Exploring the Potential of NIR Spectroscopy and Chemometrics to Verify the Flavonoid Content in Litsea cubeba - Cendekiawan, Khrisna Agung; Susanti, Dhina Ayu; Isnawati, Nafisah; Mayasari, Shinta; Riswanto, Florentinus Dika Octa (Faculty of Pharmacy, Universitas Gadjah Mada, 2025)
The ancient records about herbal medicine show traditional healing practices are deeply rooted in Indonesian culture. The medical use of plants decreased because of inheritance customs combined with the lack of written documentation on medicinal plants but dependent on oral information transmission. Traditional research and preservation activities of local healing plants which belong to specific cultural communities become possible through this phenomenon. Researchers conducted ethnopharmacological research about antidiarrheal medicinal plant uses that included traditional knowledge about flavonoid-containing plants within the Osing ethnic group of West Java Indonesia. The goal of this research was to verify flavonoid compounds in Osing's medicinal plants through Near Infra-Red (NIR) spectroscopy combined with chemometric methods. The evaluation of antidiarrheal potential for these compounds relied on flavonoid standard reference substances because these compounds demonstrate strong antioxidant properties which stabilize intestinal functioning. Chemometric techniques together with Near Infra-Red spectroscopy (NIR) were applied to analyze krangean leaves (Litsea cubeba) in order to establish their flavonoid compound levels. The quality assessment of multivariate calibration models shows that PLS regression produces RMSEC of 2.870 and RMSEP of 0.0124 with R2cal = 0.9931 and R2val = 0.9919. The analysis using linear discriminant analysis (LDA) succeeded in its completion with recognition rates above 90% for each discriminating class.